Behavioural determinants of physiologically-relevant light exposure - Anna M. Biller; Priji Balakrishnan; Manuel Spitschan (Communications Psychology)
Abstract Light exposure triggers a range of physiological and behavioural responses that can improve and challenge health and well-being. Insights from laboratory studies have recently culminated in standards and guidelines for measuring and assessing healthy light exposure, and recommendations for healthy light levels. Implicit to laboratory paradigms is a simplistic input-output relationship between light and its effects on physiology. This simplified approach ignores that humans actively shape their light exposure through behaviour. This article presents a novel framework that conceptualises light exposure as an individual behaviour to meet specific, person-based needs. Key to healthy light exposure is shaping behaviour, beyond shaping technology.